Comparison of the marginal fit of different types of dental ceramic systems (In-vitro) - Gholamreza Esfahanizadeh; Mahmood Aghel; Saeed Mohammadi Asl; Elnaz Bayat (Tehran University of Medical Sciences, 2018)
Background and Aims: Marginal gap measurement in all ceramic restorations they are of fundamental important for the successful used. As some studies led to contradiction results, yhe aim of this study is to compare marginal gap restorations between 4 kinds of ceramic restorations Inceram, IPS-e.max Press, Zirconia (CAD/CAM) and PFM. Materials and Methods: In this In-vitro experimental research, one stainless steel die with deep chamfer finish line design (1 mm depth) was prepared on a maxillary premolar. 40 epoxy resin dies were made, dies were divided in to 4 groups (n=10), Zirconia, IPS e.max press, Inceram, Mental Ceramic systems (MC). Then, the prepared crowns were put on the stainless steel die and observed their marginal mismatch under sterio microscope before cementation. Data were analyzed by One- way ANOVA, and one sample kolmogorosmirnov tests. Resultes: There was significant difference in the marginal gaps between (MC) (102.92±28.7), Inceram (98.41±24.91), IPS e.max press (128.22±25.48), and Zirconia (69.5±10.9) (P=0.0001). Conclusion: The comparison of marginal gap for the four groups was significant test. Therefore, it can be concluded that marginal gap, the probability of leakage and recurrence of caries in Zirconia systems is the least and in the IPS e.max press systems is the most.